Easy yoga : the secret to strength & balance - Cappy, Peggy; WGBH Educational Foundation; Peggy Cappy Enterprises; PBS Distribution (Firm) (Arlington, VA : Distributed by PBS Distribution, 2014)
Peggy Cappy returns with a new special that will show you how this gentle yoga program can help improve your strength and balance.
Instructor, Peggy Cappy.
TV rating: Not rated.
DVD, region 1, NTSC; stereo.
English SDH (subtitles for the deaf and hard of hearing).
Keywords: Hatha yoga; Physical fitness; Feature films; Films for the hearing impaired; Video (DVD); Instructional television programs; Instructional films